Telecommunications in economic growth of Malaysia. - Riaz, Ali (Journal of Contemporary Asia, 1997)
The writer discusses the relationship between economic growth in Malaysia and the development of the country's telecommunications industry. Malaysia has achieved rapid economic growth in recent decades, and its economy has undergone remarkable transformations. Economic progress has been accompanied by a notable improvement in the telecommunications infrastructure. Malaysia currently enjoys a state-of-the-art, very sophisticated telecommunications system. Ostensibly, the development of this infrastructure went hand in hand with Malaysia's increased level of integration into the world economy. The writer argues that there has been an intrinsic connection between the telecommunications revolution and the economic transformation: The nature of Malaysia's insertion into the global economy as well as the timing were of vital importance in the incredible expansion of telecommunications.